filmov
tv
Prove that (sin theta)/(1- cos theta)=cosec theta + cot theta
Показать описание
Prove that (sin theta)/(1- cos theta)=cosec theta + cot theta
(Sin θ)/(1-cosθ)=cosec θ+cot θ
#class10ncerttrigonometry
(Sin θ)/(1-cosθ)=cosec θ+cot θ
#class10ncerttrigonometry
Sin theta/1+Cos theta + 1+Cos theta / Sin theta = 2 Cosec theta | Mathematics Class 10 | Identity
Prove that sin θ/1-cos θ + tan θ/1+cos θ = sec θ cosec θ + cot θ
sintheta-costheta+1/sintheta+costheta-1=1/sec theta-tan theta
Prove that (sin theta)/(1- cos theta)=cosec theta + cot theta
sin square theta + cos square theta = 1 How to prove?
Prove that sin theta upon 1 + cos theta plus 1 + cos theta upon sin theta = 2 cosec theta #cbse
Prove that : sin theta - cos theta + 1/sin theta + cos theta - 1 = 1/sec theta - tan theta.
Prove that sin theta-cos theta+1/sin theta+cos theta-1 = 1/sec theta-tan theta. easy way.
Continuity and Differentiability 12 | Part 1 | One Shot in English | JEE Main & Advanced
1+Cos theta - Sin² theta /Sin theta ( 1 + Cos theta ) = Cot theta | Trigonometric Identity| Identity...
Prove that `(i) (sin theta)/((1- cos theta))=(\'cosec\' theta + cot theta) `
Prove that sin theta(1+tan theta)+cos theta(1+cot theta)=sec theta+cosec theta | Trigonometry |
If `cos theta + sin theta =1` prove that `cos theta -sin theta =+-1`
(1 + sin theta)/ cos theta + cos theta / (1 + sin theta) = 2 sec theta, verify the identity
tan theta+sec theta-1/tan theta-sec theta+1=1+sintheta/costheta
Prove :`(cos theta)/(1+sin theta) + (cos theta)/(1-sin theta)= 2 sec theta`
10th..1+cos theta+sin theta/1+cos theta-sin theta=1+sin theta/cos theta.
RD Sharma Ex 11.1 Example-7 | Prove that sin theta/(1-cos theta)+tan theta/(1+cos theta)=sec theta
Grade10 prove that ( sin theta - cos theta +1)/ sin theta + cos theta -1 = 1/ sec theta - tan theta
If (cos theta + sin theta) =1 prove that (cos theta - sin theta) = + or - 1 || Trigonometry Class-10
Prove that 1-cos theta/sin theta=sin theta/1+cos theta. Prove that sina/1-cosa=1+cosa/sina.
`(1+costheta+sintheta)/(1+costheta-sintheta)=(1+sintheta)/(costheta)`
Prove that sin theta/1-cos theta = cosec theta+cot theta | Prove that sina/1-cosa=coseca+cota |
Prove that: (1+sin theta-cos theta / 1+sin theta+cos theta)^2 = 1-cos theta / 1+cos theta
Комментарии